2007
DOI: 10.1007/s11547-007-0141-9
|View full text |Cite
|
Sign up to set email alerts
|

Contrast-enhanced MR imaging in patients with BI-RADS 3-5 microcalcifications

Abstract: Mammography and stereotactic biopsy still remain the only techniques for characterising microcalcifications. MRI cannot be considered a diagnostic tool for evaluating microcalcifications. It is, however, useful for identifying DCIS with more aggressive histological grades. An important application of MRI in patients with DCIS associated with suspicious microcalcifications could be to evaluate disease extension after a microhistological diagnosis of malignancy, as it allows a more accurate presurgical planning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
46
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(49 citation statements)
references
References 37 publications
3
46
0
Order By: Relevance
“…Published results assessing MRI-pathology concordance ranged from an underestimation rate of 0 -59 % to an overestimation rate of 7 -70 % [3,18,23,24]. Limits within which measurements on MRI are considered concordant with measurements at pathology vary and range from 0 mm -20 mm [11,[24][25][26][27].…”
Section: Discussionmentioning
confidence: 99%
“…Published results assessing MRI-pathology concordance ranged from an underestimation rate of 0 -59 % to an overestimation rate of 7 -70 % [3,18,23,24]. Limits within which measurements on MRI are considered concordant with measurements at pathology vary and range from 0 mm -20 mm [11,[24][25][26][27].…”
Section: Discussionmentioning
confidence: 99%
“…B reast magnetic resonance (MR) imaging is the most sensitive technique for depicting breast cancer, with widespread applications in screening of high-risk patients and preoperative planning (1-3). In younger women and those with dense breasts, MR imaging depicts additional disease that is occult at mammography and ultrasonography (US), both in the same and contralateral breast, and is considered more accurate for evaluating the extent of tumor (4,5). The reported incidence of additional MR imaging-detected disease in the ipsilateral breast is 3%-34%, and it is 3%-24% in the contralateral breast (6,7).…”
Section: Methodsmentioning
confidence: 99%
“…The specificity of DCE-MRI for detecting breast cancer is controversial, ranging from 21% to 100%. A previous study by Cilotti et al (26) showed no statistically significant difference between the specificities of mammography and MRI for the diagnosis of calcified lesions. In our study, the specificity of DCE-MRI alone was higher than that of FFDM alone.…”
Section: Discussionmentioning
confidence: 85%